Fire impacts on the biology of stream ecosystems A synthesis of current knowledge to guide future research and integrated fire management - Erdozain, Maitane (Global change biology, 2024)
Global Change Biology© 2024 The Author(s). Global Change Biology published by John Wiley & Sons Ltd.